Conditions for the Development of Reflexive Abilities as a Resource for the Development of Self-Determination of Students of Psychological and Pedagogical Specialties - Umnyashova, I.B. (Bulletin of Practical Psychology of Education, 2021)
The development of reflexive abilities of students is an important condition for the development of professional competence of future specialists, which affects the life and professional self-determination of studying universities. The article describes the conditions for the development of reflexive abilities of students of higher and secondary professional education organizations studying in the areas of “Education and Pedagogical Sciences” and “Psychological Sciences”: a reflexive environment as a system of conditions favorable for the development of the intellectual and personal spheres of students; reflexive activities aimed at developing skills in the analysis and evaluation of personal strategies and actions; a clear system for assessing the quality of performance of reflexive tasks and works; psychological and pedagogical support for the process of self-determination of students. It is noted that the creation of the above conditions requires certain resources, including the qualifications of university employees in the field of organizing the developing educational environment of an educational institution, material, technical and organizational conditions, and the university has an expanded network of social partners. Развитие рефлексивных способностей студентов является важным условием развития профессиональной компетентности будущих специалистов, влияющим на жизненное и профессиональное самоопределение обучающихся вузов. В статье представлено описание условий развития рефлексивных способностей студентов организаций высшего и среднего профессионального образования, обучающихся по направлениям «Образование и педагогические науки» и «Психологические науки»: рефлексивная среда как система условий, благоприятных для развития интеллектуальной и личностной сфер обучающихся; рефлексивная деятельность, направленная на развитие навыков анализа и оценки личностных стратегий и действий; четкая система оценивания качества выполнения рефлексивных заданий и работ; психолого-педагогическая поддержка процесса самоопределения студентов. Отмечается, что создание перечисленных выше условий требует определенных ресурсов, в том числе квалификации сотрудников вуза в области организации развивающей образовательной среды образовательного учреждения, материально-технических и организационных условий, наличия у вуза расширенной сети социальных партнеров.